Establishment and characterization of a novel highly malignant lung cancer cell line ZX2021H derived from a metastatic lymph node lesion. Issue 8 (16th March 2022) - Zu, Lingling; Li, Xuebing; He, Jinling; Zhou, Ning; Meng, Fanrong; Li, Xiaozhou; Xu, Song; Zhang, Lei
Abstract: Background: Lung cancer is a highly malignant tumor with a poor prognosis. The establishment of faithful ex vivo cell models is essential for investigating the metastatic mechanisms and developing new anticancer agents. In this study, we established and characterized a novel lung cancer cell line derived from metastatic lymph node tissue from a Chinese patient. Methods: A primary culture of metastatic lymph node tissue from a patient with lung cancer was used to establish a cell line. The phenotypic characteristics of the cell line were characterized by colony‐formation, CCK8, and Transwell assays, and xenografting. The genetic characteristics were evaluated by chromosome analysis, short tandem repeat (STR) profiling, and quantitative real time‐polymerase chain reaction (qRT‐PCR). Results: A novel lung cancer cell line, named ZX2021H, was successfully established from a metastatic lymph node lesion from a lung cancer patient. The cell line exhibited high capacities for proliferation and invasion, as validated by its phenotypic and genetic characteristics. This cell line had a unique STR profile and karyotype analysis revealed numerical and structural chromosome abnormalities. The growth rate of in vivo xenografted tumors established using ZX2021H cells was higher than that using H1299 cells. The cell stemness‐related gene SOX2 was overexpressed in ZX2021 compared with H1299 cells, as determined by qRT‐PCR. Conclusion: We successfully established a novel, highly malignant lung cancer cell line, ZX2021H, derived from metastatic lymph node tissue from a Chinese lung cancer patient. This cell line may provide an ideal cell model for further studies of the molecular mechanisms underlying lung cancer metastasis and for the development of new anticancer agents. Abstract : The lymph node has been generally considered an organ prone to metastasize in lung cancer. Establishment and characterization of a novel highly malignant lung cancer cell line ZX2021H derived from a metastatic lymph node lesion